Mainstreaming Of Islamic Moderation In Higher Education: The Radical Experience Conter - Fuad, A. Jauhar; Susilo, Suko (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
This paper explains the mainstreaming of Islamic moderation in tertiary institutions as part of the counter of radical understanding which has recently been strengthened. First, mainstreaming Islamic moderation as a new paradigm by making regulations on subjects, dress codes, declarations of lecturer associations as a commitment to counter radicalism. Second, in the process of mainstreaming Islamic moderation starting from the mechanism of student admission and welcoming students with various series of orientation of the period of new student admissions. The activity agenda is longer compared to other campuses in general. Third, the mainstreaming of Islamic moderation is carried out by developing an Islamic religion curriculum that is taught for six semesters in general study programs. In the learning process, it is more focused on the discussion method by utilizing various learning media; and the process of knowledge integration